Ergonomics Risk Factors at Manufacturing Industry: A Prelude Study - Isa, Halim (2009)
Manufacturing industry has been recognized as a vital contributor to nation economy as it offers enormous job opportunities to local and foreign workers. In recognition the importance of manufacturing industry, workplaces should be designed ergonomically so that workers could perform jobs in a healthy working environment. The objectives of the current research are to identify ergonomics risk factors present in the related industries and propose a solution to minimize the risk of occupational injuries. The objectives are achieved through an ergonomics survey conducted in a metal stamping company that utilised video recording and face to face interviews with production workers to reveal the real situation. Based on the survey, there are evident that workers have been exposed to ergonomics risk factors associated with awkward working posture. Working posture assessment is performed and adjustable workstation is proposed as a control measure to minimize occupational injuries associated with awkward working posture. The research concluded that the redesign of the workstation has shown potential solution for a safe working posture.